Multi-sensor system for monitoring of river water pollution - Evizal, A.K. (Wydawnictwo SIGMA-NOT, 2020)
Rivers play significant roles in communities, including as source of drinking water and for transportation and other daily activities. However, water pollution is a major problem in several communities, with significant negative consequences to health and well-being and socioeconomic development. This research, therefore, aimed to design and develop a system with multiple sensors to monitor river water pollution because most communities use river water in their daily activities. In the design and development of the system, multiple sensor nodes were installed for the detection of water pollution parameters such as temperature, Electrical Conductivity (EC), water pH, and Dissolved Oxygen (DO). The system was designed to monitor river water pollution parameters and send the information to the data centre (backend system). Arduino microcontroller was used to process and filter the data before sending to the backend system. Only valuable information was collected and kept in the database. Results: show that the system was able to detect polluted water by showing the parameters of interest in a graph. The polluted water indicators were mostly contributed from residential waste and industries. This work has furnished progress in the development and validation of appropriate technologies for tackling river water pollution. In the future, WSNs sensors will be deployed in some areas and the results across the different areas will be compared. Furthermore, the Internet of Things (IoT) Technology will be used for data sharing and communication. Â© 2020 Wydawnictwo SIGMA-NOT. All rights reserved.